Optical and energy dependent response of the alanine gel solution produced at IPEN to clinical photons and electrons beams - Silva, Cléber F.; Campos, Letícia L. (Revista Brasileira de Física Médica, 2015)
The DL-Alanine (C3 H7 NO2 ) is an amino acid tissue equivalent traditionally used as standard dosimetric material in EPR dosimetry. Recently, it has been studied to be applied in gel dosimetry, considering that the addition of Alanine in the Fricke gel solution improves the production of ferric ions radiation induced. The spectrophotometric evaluation technique can be used comparing the two spectrum wavelengths bands: 457 nm band that corresponds to ferrous ions and 588 nm band that corresponds to ferric ions concentration to evaluate the dosimetric properties of this material. The performance of the Alanine gel solution developed at IPEN has been firstly studied using the spectrophotometric technique aiming to apply this material to 3D clinical doses evaluations using MRI technique. In this work, the optical and the energy dependent response of this solution submitted to clinical photons and electrons beams were studied. Different batches of gel solutions were prepared and maintained at low temperature during 12 h to solidification. Before irradiation, the samples were maintained during 1 h at room temperature. The photons and electrons irradiations were carried out using a Varian 2100C Medical Linear Accelerator of the Radiotherapy Department of the Hospital das Clínicas of the University of São Paulo with absorbed doses between 1 and 40 Gy; radiation field of 10 x 10 cm2 ; photon energies of 6 MeV and 15 MeV; and electron with energies between 6 and 15 MeV. The obtained results indicate that signal response dependence for clinical photons and electrons beams, to the same doses, for Alanine gel dosimeter is better than 3.6 % (1σ), and the energy dependence response, to the same doses, is better 3% (1σ) for both beams. These results indicate that the same calibration factor can be used and the optical response is energy independent in the studied dose range and clinical photons and electrons beams energies,